Oleia fieldsi sp. n., a new Orthocladiinae (Diptera: Chironomidae) species from the Brazilian Atlantic rainforest - Da Silva, Fabio Laurindo; Song, Chao (Zootaxa, 2018)
One new species of the genus Oleia Andersen et Mendes, 2007 (Diptera: Chironomidae: Orthocladiinae), O. fieldsi sp. n. is described and figured as adult male. The specimens were collected in a fragment of secondary forest in the Atlantic Forest, at Iguaçu National Park, on the border of Argentina and Brazil.